Optimal Dexmedetomidine Dose to Prevent Emergence Agitation Under Sevoflurane and Remifentanil Anesthesia During Pediatric Tonsillectomy and Adenoidectomy - Zhang, Yan-zhuo; Wang, Xue; Wu, Jia-min; Song, Chun-yu; Cui, Xiao-guang (Frontiers in Pharmacology, 2019)
Background: Emergence agitation (EA) is a common pediatric complication after sevoflurane anesthesia that can be prevented with dexmedetomidine. However, an inappropriate dose of dexmedetomidine can cause prolonged sedation and cardiovascular complications. Thus, we evaluated the optimal dose (ED95) of dexmedetomidine for preventing EA with sevoflurane and remifentanil anesthesia after pediatric tonsillectomy and adenoidectomy. Methods: We enrolled ASAI-II children 3–7 years of age who underwent tonsillectomy with adenoidectomy. During induction, dexmedetomidine was infused for 10 minutes. Anesthesia was induced with sevoflurane and maintained with sevoflurane and remifentanil resulting in a Bispectral spectrum (BIS) range from 40–60. Extubation time, surgical and anesthetic duration time, and duration time in the post-anesthesia care unit (PACU) stay were recorded. EA (measured with Pediatric emergence delirium PAED scores) and pain (measured with (face, legs, activity, cry, Consolability) FLACC scores) were assessed at extubation (E0), and 15 minutes after extubation (E1) and 30 minutes after extubation (E2). If EA occurred, the next surgical procedure included increased dexmedetomidine by 0.1 μg/kg, and if not, the drug was reduced by 0.1 μg/kg. Results: The 50% effective dose (ED50) of dexmedetomidine for preventing EA after sevoflurane and remifentanil anesthesia for tonsillectomy and adenoidectomy was 0.13 μg/kg, its 95% confidence interval is 0.09 0.19 μg/kg, and ED95 was 0.30 μg/kg, its 95% confidence interval is 0.21 1.00μg/kg. Conclusion: Intravenous dexmedetomidine infusion at ED50 (0.13 μg/kg) or ED95 (0.30 μg/kg) during induction for 10 minutes can prevent half or almost all EA after sevoflurane and remifentanil anesthesia during pediatric tonsillectomy and adenoidectomy.